2020
DOI: 10.19110/geov.2020.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Why mineral carriers are necessary for microalgae

Abstract: Abiotic, biotic and anthropogenic factors inhibit normal life of microorganisms. We have presented that the mineral carrier provides integrity and increases the growth of microalgal cells under stress conditions. Microalgae Chlorella vulgaris, immobilized on an analcime-containing rocks (biogeosorbent), are resistant to increased salinity (34 ‰) and organic pollutants (phenolic water with a concentration of 10 μg/dm 3 ). The advantage of the synergetic complex of the biogeosorbent from its individual component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…2), and also because of relatively constant chemical and mineral composition in comparison with technogenic analogues. The material composition of clays and zeolites is well studied and, as mineral carriers, they have a high adsorption activity [19]. The specific surface area varies from 10.38 to 51.69 m 2 /g.…”
Section: Natural Aluminosilicatesmentioning
confidence: 99%
See 3 more Smart Citations
“…2), and also because of relatively constant chemical and mineral composition in comparison with technogenic analogues. The material composition of clays and zeolites is well studied and, as mineral carriers, they have a high adsorption activity [19]. The specific surface area varies from 10.38 to 51.69 m 2 /g.…”
Section: Natural Aluminosilicatesmentioning
confidence: 99%
“…The relevance of studying the interphase interaction, which determines the main technological properties of nanocomposites (other nanostructures) based on aluminosilicate raw materials in the course of synthesis processes, is extremely high. Potentially available, and also used practically today, aluminosilicate components for the synthesis (production) of industrially significant products are classified into 3 categories: technogenic, synthetic and natural [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The diversity and prevalence of aluminosilicates makes them promising test objects.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We showed that the mineral carrier ensured safety and increases the growth of microalgae cells under stress conditions. Microalgae Chlorella vulgaris immobilized on analcimecontaining rocks showed tolerance to increased salinity (34 ‰) and organic pollutants (phenolic water with a concen tration of 10 μg/dm 3 ) [8].…”
mentioning
confidence: 99%